Strain Degeneration in Pleurotus ostreatus: A Genotype Dependent Oxidative Stress Process Which Triggers Oxidative Stress, Cellular Detoxifying and Cell Wall Reshaping Genes - Gumer Pérez; Federico Lopez-Moya; Emilia Chuina; María Ibañez-Vea; Edurne Garde; Luis V. López-Llorca; Antonio G. Pisabarro; Lucía Ramírez (Journal of Fungi, 2021)
Strain degeneration has been defined as a decrease or loss in the yield of important commercial traits resulting from subsequent culture, which ultimately leads to Reactive Oxygen Species (ROS) production. Pleurotus ostreatus is a lignin-producing nematophagous edible mushroom. Mycelia for mushroom production are usually maintained in subsequent culture in solid media and frequently show symptoms of strain degeneration. The dikaryotic strain P. ostreatus (DkN001) has been used in our lab as a model organism for different purposes. Hence, different tools have been developed to uncover genetic and molecular aspects of this fungus. In this work, strain degeneration was studied in a full-sib monokaryotic progeny of the DkN001 strain with fast (F) and slow (S) growth rates by using different experimental approaches (light microscopy, malondialdehyde levels, whole-genome transcriptome analysis, and chitosan effect on monokaryotic mycelia). The results obtained showed that: (i) strain degeneration in P. ostreatus is linked to oxidative stress, (ii) the oxidative stress response in monokaryons is genotype dependent, (iii) stress and detoxifying genes are highly expressed in S monokaryons with symptoms of strain degeneration, (iv) chitosan addition to F and S monokaryons uncovered the constitutive expression of both oxidative stress and cellular detoxifying genes in S monokaryon strains which suggest their adaptation to oxidative stress, and (v) the overexpression of the cell wall genes, Uap1 and Cda1, in S monokaryons with strain degeneration phenotype indicates cell wall reshaping and the activation of High Osmolarity Glycerol (HOG) and Cell Wall Integrity (CWI) pathways. These results could constitute a hallmark for mushroom producers to distinguish strain degeneration in commercial mushrooms.